Numerical investigation on structural behaviour of steel beams under elevated temperature - Cinitha, A.; Umesha, P.K.; Iyer, Nagesh R. (Journal of Structural Engineering, 2024)
The recent fire hazards of structures in Indian cities alarmed civil engineering community and demanded the perspective research on behaviour of steel structures under elevated temperature. The analysis of structural members on a compartment in a steel frame building subjected to fire attack is often difficult owing to the combined complexity of the material degradation and of the actions induced by thermal strains. Owing to the complexity of the design and analysis of structures under elevated temperature, the compartment concept has been favoured in many contemporary research investigations. Further it also offers considerable promise as a methodology that leads to perspective codified design rules. The deformation of steel structures will be caused due to several reasons and it depends upon the material properties of steel and temperature conditions. Hence, it is important to assess the behaviour of steel structures under elevated temperature. This paper studies behaviour of steel beam, which is part of a thermal power plant structure subjected to elevated temperature in a framed compartment by finite element method. The study involves two-sided, three-sided and four-sided exposure conditions. A profound variation in response is observed under the combination of thermal actions and end restraints. A critical review on responses of characteristic properties of structural steel under elevated temperature is highlighted. An attempt to illustrate some of the most important and fundamental principles that govern the behaviour of structural steel elements under elevated temperature are carried out.